Inflammation in the Pathophysiology and Therapy of Cardiometabolic Disease - Donath, Marc Y (Endocr Rev, 2019)
The role of chronic inflammation in the pathogenesis of type 2 diabetes mellitus and associated complications is now well established. Therapeutic interventions counteracting metabolic inflammation improve insulin secretion and action and glucose control and may prevent long-term complications. Thus, a number of anti-inflammatory drugs approved for the treatment of other inflammatory conditions are evaluated in patients with metabolic syndrome. Most advanced are clinical studies with IL-1 antagonists showing improved β-cell function and glycemia and prevention of cardiovascular diseases and heart failure. However, alternative anti-inflammatory treatments, alone or in combinations, may turn out to be more effective, depending on genetic predispositions, duration, and manifestation of the disease. Thus, there is a great need for comprehensive and well-designed clinical studies to implement anti-inflammatory drugs in the treatment of patients with metabolic syndrome and its associated conditions.